2008
DOI: 10.4219/jeg-2008-819
|View full text |Cite
|
Sign up to set email alerts
|

What Language Discourse Tells us about Bilingual Adolescents: A Study of Students in Gifted Programs and Students in General Education Programs

Abstract: the latino/a population of the United States continues to increase dramatically; consequently, educators face the challenge of how best to provide educational services for those whose primary language is Spanish. the purpose of this study was to examine student discourse between bilingual students in gifted programs and bilingual students in the general education programs in an urban middle school. this study suggests a minor language advantage for the bilingual students in the gifted program. the overall conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
10
0
2
Order By: Relevance
“…(Wu & Elliott, 2008, p. 233) Ackerman (1997; Ash and Huebner (1998); Bain and Bell (2004); Brice et al (2008); L. K. S. Chan (1996); Dai (2001); Gentry et al (2000); Hawkins (1997); Klein and Zehms (1996); Lea-Wood and Clunies-Ross (1995); Maksic (1997); Shaunessy et al (2007); Shaunessy et al (2006); Shavinina and Kholodnaja (1996); Shaywitz et al (2001); Thornton et al (2006); Threlfall and Hargreaves (2008); Tong and Yewchuk (1996); Udvari and Rubin (1996); Wu and Elliott (2008); Zeidner et al (2005) Additional sources of evidence "Students who said that they had been identified as gifted in high school and had taken Advanced Placement courses were considered high-ability for the purposes of this experiment." (Nikolova & Taylor, 2003, p. 208) Ackerman (1997; …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(Wu & Elliott, 2008, p. 233) Ackerman (1997; Ash and Huebner (1998); Bain and Bell (2004); Brice et al (2008); L. K. S. Chan (1996); Dai (2001); Gentry et al (2000); Hawkins (1997); Klein and Zehms (1996); Lea-Wood and Clunies-Ross (1995); Maksic (1997); Shaunessy et al (2007); Shaunessy et al (2006); Shavinina and Kholodnaja (1996); Shaywitz et al (2001); Thornton et al (2006); Threlfall and Hargreaves (2008); Tong and Yewchuk (1996); Udvari and Rubin (1996); Wu and Elliott (2008); Zeidner et al (2005) Additional sources of evidence "Students who said that they had been identified as gifted in high school and had taken Advanced Placement courses were considered high-ability for the purposes of this experiment." (Nikolova & Taylor, 2003, p. 208) Ackerman (1997; …”
Section: Discussionmentioning
confidence: 99%
“…(a) parent, teacher, or peer referral" (Brice et al, 2008, p. 13) Ackerman (1997; Brice et al (2008); L. K. S. Chan (1996); Gentry et al (2000); Klein and Zehms (1996); Shaunessy et al (2007); Shaunessy et al (2006); Shaywitz et al (2001); Udvari and Rubin (1996) Extracurricular activities "In addition to a high IQ, students must have outstanding academic achievements in science or mathematics or in the artistic domain. Based on an interview prior to the experiment, the students could be classified into three groups: (1) Six students were talented in the field of literature; they had published poems, short stories, or novels;…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This escalates as gifted students mature (Van Tassel-Baska, 2002), with neural networks impacting both visual and sound representation in both hemispheres of the brain (Katzir & Pre-Blagoev, 2006). Their comprehension in verbal and written communication, with application to reading, discourse, morphology, interpretation, and the use of advanced syntax are important aspects of high ability in language arts (Brice et al, 2008;Tyler, 2005), and require differentiated approaches to teaching gifted children in order to maximize verbal potential.…”
Section: Language Arts For Gifted Studentsmentioning
confidence: 99%